Flow enhancement using structured physical-chemically interacted polymer surfactant complex - Fakhrulddin, Sarmad Kamal (2018)
In this study, the DR of surfactant-polymer complex at similar and different charges and concentrations in aqueous systems under turbulent flow was investigated. Copolymer of acrylamide and sodium acrylate (PAM) which are an anionic polymer and non-ionic polyethylene oxide (PEO) were used in this study. The surfactants used in the study are hexadecyl trimethyl ammonium chloride (HTAC) which is a cationic surfactant and sodium dodecyl benzene sulfonate (SDBS) which is an anionic surfactant. The effect of their complexes (PAM-SDBS, PAM-HTAC, PEO-SDBS, and PEO-HTAC) was also investigated for DR effect. A new approach for the determination of the limitations of DR through the control of the physical properties of the polymers and surfactant and their complexes were suggested in this study. This study is partitioned into five experimental phases which are: (i) experiments on the electrical conductivity to determine the interaction range, and the kinematic viscosity to evaluate the interaction behaviour of the additives; (ii) experiments using the rotating disk apparatus (RDA) to evaluate the efficiency of the additives and their respective stabilities under an extended shear rate in DR applications; (iii) experiments on testing the flow enhancement performance of the polymer-surfactant complexes in terms of the flow rate, additives concentrations, complexes formation concentrations, shear rate, and velocity distribution in pipe flow; (iv) experiments using the MicroPro laser Doppler velocimeter (MLDV) technique to calculate the flow velocity in the pipes and flow amenities of any size near to a wall and (v) experimental data were presented in term of statistically expression using statistical package for the social sciences (SPSS) software. The studies on the electrical conductivity and viscosity assessment showed that even though the interaction between the polymer and surfactant was more pronounced when evaluated using viscosity tests, a minimal deviation in the obtained data was observed at higher PEO concentrations. A strong relationship was observed between the viscosity of the system and the recorded DR performance. The results of the RDA and pipeline studies generally showed different patterns based on the polymer-surfactant parameters. There were pronounced effects on the viscosity and DR of the flow system which are mainly due to the strong interaction between the opposite charges of polymers and surfactants. The degradation resistance of PEO was found to improve with the addition of surfactants. The results showed a different trend (increase or decrease) in DR% depending on many parameters such as the polymer concentration, surfactant concentration, complex combination, charge interaction, and polymer-surfactant concentration ratio. A maximum DR of 54% was observed at a combination of 40 ppm of PEO with 100 ppm of HTAC. In the interaction of complexes using PEO with surfactant, the drag reduction was observed to increase after the interaction point critical aggregation concentration (CAC). However, the improvement in DR was noticed to decrease back again even when the concentration was still below the polymer saturation point (PSP). The MLDV studies showed that the change in the turbulent structure was due to the modification of the velocity profile in the region near the wall when adding micelle surfactants to the polymer chain which describes the theory. According to the morphology images using Cryo-Transmission electron microscopy (Cryo-TEM), the results have confirmed the interaction between polymer and surfactant on the formation of the complexes that clearly explains the enhanced flow behavior reported by the RDA and the pipe studies. This study, concludes that there is a need to maintain the right concentration of the polymer and surfactant in the system for a better DR when using the combined polymer-surfactant approach.